Awareness Level of Operating Room Nurses of Their Professional Tasks - Hannani, Sedigheh; Kamali, Nasrin; Kashaninia, Zahra; Hosseini, Agha Fatemeh; Ebrahimi, Abed; Gholam Veisi, Behzad; Sadeghi, Mostafa (Advances in Nursing & Midwifery, 2020)
Introduction: The awareness of the duties and responsibilities of operating rooms nurses is considered as a basis for systems monitoring and quality evaluation. Operating room nurses are supposed to be aware of their professional standards and achieve their functions following professional standards. Methods: This cross-sectional study was carried out based on the census and sampling with 143 operating room nurses working in nine training hospitals of Iran University of Medical Sciences. The research instrument was a researcher-made questionnaire, and the reliability was assessed through Cronbach’s alpha. Also, both face and content validity of the questionnaire have been checked by faculty members. Data were analyzed by SPSS version 19 with descriptive statistics, Chi-square test, and Pearson’s correlation coefficient. Results: In terms of preoperative responsibilities, 25.7%, 35.9%, and 38.3% of operating room nurses experienced the awareness levels of high, moderate, and weak, respectively. The awareness levels for 20.4%, 34.7%, and 44.9% of operating room nurses were evaluated as high, moderate, and weak, respectively. They were considering the post-operative responsibilities of operating room nurses, 32.3%, 32.3%, and 35.3% of operating room nurses who experienced the awareness levels of high, moderate, and weak, respectively. Conclusions: The results indicated that a vast majority of operating room nurses experienced a high level of awareness with respect to their responsibilities before, during, and after the operation. Nurses’ awareness of their mission, and management and official plans for promoting deficiencies in this regard could help promote health. Contextualized education on improving the quality of nursing services should be considered as a part of the training for OR nurses and suggested to investigate the awareness level of nurses and other treatment staff about the standards of their responsibilities in diverse sectors to perform suitable planning of tasks.